The power of peers: mobile youth culture, homophily and informal learning among a group of South African youth - Carew, Joanne (Centre for Film and Media Studies, 2017)
Popular notions of "net generations" and "digital natives" have already been subject to sustained academic critique. This dissertation builds on such critiques by documenting the local practices and distinctive mobile literacies of a group of young people in South Africa. These young people (ages 13-17, n=18) were asked how they were learning about and using ICTs. The sample lived in Makhaza, Khayelitsha, and were members of a non-profit youth development organisation, Ikamva Youth, participating in beginner coding classes. This study explored what they had already learned about ICTs from their networks of close interpersonal relationships (n=133) and asked them how they felt about their own ICT knowledge, as well as the ICT skills of those around them. Unlike their wealthier counterparts, such young people do not have ubiquitous Internet connectivity, ease of access to consumer electronics or many opportunities to learn about computers in particular. Yet, rather than being stuck on the wrong side of a 'digital divide' or waiting passively for government to fulfil broken promises about digital literacy in schools, they were actively pursuing knowledge about ICTs and mobiles in particular. They demonstrated distinctive 'mobile-centric' repertoires, fostered through learning about ICTs from their strong ties. This gave rise to a distinctive mobile youth culture, shaped by race, class, and gender dynamics. Gendered biases and preoccupations, peer networks and technicities were particularly important. While this allows many creative and strategic appropriations of mobile technology, it also means that largely homophilous informal learning networks in part set the bounds of their learning. When most of what you're learning comes from your friends, it really matters who those friends are. Unsurprisingly, gaps in their digital literacies were apparent. In particular, their ability to fully participate in modern digital publics is curtailed. It remains essential to provide formal opportunities for young people to learn about ICTs at school, but also informally via a larger network of interpersonal relationships and communities of practice such as Ikamva Youth. Mobile technology presents many opportunities and suggests new approaches to digital literacy. Nonetheless, it seems likely that, given difficulties in accessing high status ICTs and bridging capital in particular, access and knowledge gaps will continue to disadvantage such young people.